Structure activity relationships leading to the identification of the indirect activator of AMPK, R419. (1st October 2022) - Shaw, Simon J.; Goff, Dane A.; Carroll, David C.; Singh, Rajinder; Sweeny, David J.; Park, Gary; Jenkins, Yonchu; Markovtsov, Vadim; Sun, Tian-Qiang; Issakani, Sarkiz D.; Hitoshi, Yasumichi; Payan, Donald G.
Graphical abstract: Abstract: Using an in-cell AMPK activation assay, we have developed structure–activity relationships around a hit pyridine dicarboxamide 5 that resulted in 40 (R419). A particular focus was to retain the on-target potency while also improving microsomal stability and reducing off-target activities, including hERG inhibition. We were able to show that removing a tertiary amino group from the piperazine unit of hit compound 5 improved microsomal stability while hERG inhibition was improved by modifying the substitution of the central core pyridine ring. The SAR resulted in 40, which continues to maintain on-target potency. Compound 40 was able to activate AMPK in vivo after oral administration and showed efficacy in animal models investigating activation of AMPK as a therapy for glucose control (both db/db and DIO mouse models).